2019
DOI: 10.1108/ijm-10-2018-0345
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and career growth

Abstract: Purpose The purpose of this paper is to examine the instrumental use of social capital regarding career growth within an organization, focusing on the mediating role of perceived competence mobilization and the moderating role of two situational variables: perceived external prestige and job insecurity climate. Design/methodology/approach Relationships among the constructs are predicted based on relevant literature, and are tested using survey results from 324 employees working in 14 leading corporations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Third, social capital mediated the relationships among supervisor-supportive organizational climate, pressure to produce, organizational climate, and service performance, while organizational silence mediated the relationship between a formalized organizational climate and innovative behavior. Social capital is an essential concept in social science [73]. This study found that organizational silence had no mediating effect on the relationship between a formalized organizational climate and innovative behavior in the Chinese and Korean samples.…”
Section: Discussionmentioning
confidence: 64%
“…Third, social capital mediated the relationships among supervisor-supportive organizational climate, pressure to produce, organizational climate, and service performance, while organizational silence mediated the relationship between a formalized organizational climate and innovative behavior. Social capital is an essential concept in social science [73]. This study found that organizational silence had no mediating effect on the relationship between a formalized organizational climate and innovative behavior in the Chinese and Korean samples.…”
Section: Discussionmentioning
confidence: 64%
“…The study results also reinforce existing studies identifying social intelligence as a valued individual quality. Social intelligence is already associated with greater self-awareness (Burdorf et al ., 2020); self-acceptance; sense of meaning; personal growth (Ryff, 2014); emotional intelligence; improved mental health (Malinauskas and Malinauskiene, 2018) and career growth (Kang et al ., 2019). By identifying social intelligence as a means to combat stress and withdrawal intentions, the study adds to the literature highlighting the importance of social intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Contextual influences studied as moderators include climate-like constructs, such as innovation climate (Jiang et al, 2020a(Jiang et al, , 2020b, job insecurity climate (Kang et al, 2019), perceptions on organizational politics (Wanniarachchi et al, 2020;Liu et al, 2010) and shared vision (Huang et al, 2017). The career-related moderators examined are career growth (Ingusci et al, 2019), career growth opportunities (Bashir et al, 2020) and perceived alternative job opportunities (Zhu et al, 2020).…”
Section: Integrative Reviewmentioning
confidence: 99%
“…Most of the scholars in career growth literature studied variables at the individual level. Though prior research considered various contextual variables as moderators, such as innovation climate (Jiang et al, 2020a(Jiang et al, , 2020b, job insecurity climate (Kang et al, 2019) and perceptions of organizational politics (Liu et al, 2010), only innovation climate was collected at the individual level and aggregated to the organization level. This type of cross-level type of study is scarce in career growth literature.…”
Section: Integrative Reviewmentioning
confidence: 99%
See 1 more Smart Citation